Formulation and In-Vitro Evaluation of Oxcarbazepine Liquisolid Compacts - Tiwari, Deeksha; Sharma, Vandana; Soni, S. L (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: The solubility and dissolution properties of any drug are fundamental determinants of its oral bioavailability. The dissolution rate of weakly soluble, highly permeable (BCS-II) drugs, such as Oxcarbazepine, be capable of enhanced by use of the liquisolid (LS)technique Methods: Oxcarbazepine liquid-solid compacts were formulated using PEG-600 as the non-volatile solvent, Avicel 102 as the carrier material, Aerosil 200 as the coating material Sodium starch glycolate as the disintegrant. Various batches of liquisolid compacts were set up by utilizing varied carrier-coating excipient ratio and different concentration of liquid medication. Flow parameters such as bulk density, tapped density, Carr’s Index, Hausner’s Ratio as well as an angle of repose were utilized to test the flowability of the powder mix. The liquid-solid system were made by direct compression strategy and were assessed for tests, for example weight variation, drug content, hardness, thickness, friability, wetting time, breaking down time also as well as the in vitro dissolution studies. Results: The liquisolid system showed acceptable micromeritic properties. The tabletting properties of the liquisolid compacts were within the acceptable limits. delivery paces of liquisolid compacts were obviously higher compared with directly compressed tablets, due to expanding wetting properties and surface area of the drug. The liquisolid compacts showed enhanced bioavailability when compared with their conventional formulation Conclusion: Liquid-solid tablet was measured as a hopeful system to enhance solubility and dissolution rate of poor-water soluble Oxcarbazepine.